Snakebite-Associated Infections: A Systematic Review and Meta-Analysis - Bonilla-Aldana, D. Katterine (2024)
Snakebites still constitute a significant public health problem in developing countries and are considered a neglected tropical condition by the WHO. Snake accidents are associated with substantial morbidity and mortality and may produce secondary complications, such as severe infections. The objective of this systematic review was to determine the prevalence of snakebite infections and characterize the bacteria isolated from these infections. A systematic literature review in five databases was carried out to assess the prevalence of snakebite infection. A meta-analysis was performed using a random-effects model to calculate the pooled prevalence and 95% CIs. Cochran’s Q test and the I2 statistic were used to assess between-study heterogeneity. The pooled prevalence of infection due to snakebite was 27.0% (95% CI: 22.0–32.0%), with high heterogeneity among studies (I2 5 99.7%). The prevalence was higher in Asia (32%) than in the Americas (21%). Snakebite infections required surgical interventions in 68% (95% CI: 37.0–98.0%). The leading group of pathogens identified corresponded to Gram-negative bacteria (63%), particularly Morganella morganii (32%), but also, Gram-positive cocci (40%), especially Enterococcus spp. (23%) and Staphylococcus aureus (15%). However, multiple other pathogens, including anaerobes, were found. A high prevalence of snakebite-associated infection has been described, primarily due to M. morganii, with the corresponding implications for empirical therapy. Rational use of antimicrobials is recommended, and this should guide initial empirical treatment. Moreover, isolation and identification of the possible bacteria present in snakebite wounds is recommended in all cases to confirm or rule out associated infection.